MEDIA OWNERSHIP AND DEMOCRACY PROCESSES IN INDONESIA - ., Firman; Rahmawati, Restu (Pusat Riset Politik BRIN, 2023)
This paper highlights the impact of media ownership on the democratic process in Indonesia. The research employs literature analysis and case studies to gather data from various relevant sources. The findings indicate that the concentration of media ownership significantly affects democracy in Indonesia, in the sense that it may lead to a proliferation of biased information and opinions, while simultaneously hampering the diversity of perspectives within society. However, these risks can be mitigated by sustaining press freedom, effective regulations, and strong public participation; Transparency, accountability, and robust media freedom are highly necessary to ensure a healthy diversity of media ownership and equitable information distribution in Indonesia. The article concludes that it is important to continuously monitor and study the relationship between media ownership and political influence within the context of democracy in Indonesia. Collaboration among the government, media, and civil society is key to maintaining a healthy balance between media freedom and the protection of a diverse and inclusive democratic process